Serviceability limit verification for structural elements of steel hall - Skrzypczak, Izabela; Oleniacz, Grzegorz (International Conference “Environmental Engineering”, 2017)
In recent years, the importance of assessing structural reliability has increased significantly. This is confirmed by the recommendations of the PN-EN 1990 standard. This standard gives the principles and requirements to ensure the safety, serviceability and durability of the structure. It sets out the basis for calculation and verification of the structure and provides guidance to ensure their reliability. Reliability of structure is its ability to meet specific design requirements, taking into account the planned period of use. The planned period of use should be understood as a time period approved in the project, in which the structure or part of it is to be used for their intended purpose, without the need for major repairs. Typically, reliability is expressed by probabilistic measures as indicator of reliability or probability of failure. The aim of this study is to present the results of of roof girder deflection surveying and modeling their reliability. A general algorithm for determining the value of the reliability indicator for the bending steel beam with FORM method will be presented. Verification of the differences between the indicator of reliability obtained by simplified probabilistic methods and compare them with the values recommended in the Eurocode 0 standard will be also shown. For the analyzed steel beam the serviceability limit states were considered.
Keywords: serviceability limit; reliability of structure; roof girder deflection surveying